7β-Methyl substituent is a structural locus associated with activity cliff for nepenthone analogues. Issue 14 (7th August 2018) - Sun, Hui-jiao; Wang, Yu-hua; Yuan, Cong-min; Kong, Ling-hui; Xu, Xue-jun; Wang, Yu-jun; Wu, Hai-hao; Lin, Cheng; Qian, Yuan-yuan; Huang, Huo-ming; Xiao, Li; Liu, Xiao; et al.
Graphical abstract: Highlights: A series of 7 β -methyl-nepenthone analogues were designed by hybridization. The binding and functional assays on opioid receptors were performed. The 7 β -methyl of nepenthone analogues was identified associated with activity cliff. 7 β -Methyl produces different activity changes for nepenthone and orvinol analogues. The possible molecular mechanism was proposed for the pharmacological heterogeneity. Abstract: With the purpose of identifying novel selective κ opioid receptor (KOR) antagonists as potential antidepressants from nepenthone analogues, starting from N -nor- N -cyclopropylmethyl-nepenthone (SLL-020ACP), a highly selective and potent KOR agonist, a series of 7 β -methyl-nepenthone analogues was conceived, synthesized and assayed on opioid receptors based on the concept of hybridization. According to the pharmacological results, the functional reversal observed in orvinol analogues by introduction of 7 β -methyl substituent could not be reproduced in nepenthone analogues. Alternatively, introduction of 7 β -methyl substituent was associated with substantial loss of both subtype selectivity and potency but not efficacy for nepenthone analogues, which was not found in 7 β -methyl orvinol analogues. Surprisingly, SLL-603, a 7 β -methyl analogue of SLL-020ACP, was identified to be a KOR full agonist. The possible molecular mechanism for the heterogeneity in activity cliff was also investigated. In conclusion, 7 β -methyl substituent was a structural locus associated with activity cliff and demonstrated as a pharmacological heterogeneity between nepenthone and orvinol analogues that warrants further investigations.